Strong antitumor efficacy of a pancreatic tumor‐targeting oncolytic adenovirus for neuroendocrine tumors. (21st September 2017) - Yamamoto, Yuki; Nagasato, Masaki; Rin, Yosei; Henmi, Marina; Ino, Yoshinori; Yachida, Shinichi; Ohki, Rieko; Hiraoka, Nobuyoshi; Tagawa, Masatoshi; Aoki, Kazunori
Abstract : We have previously identified a pancreatic cancer‐targeting peptide ligand and demonstrated that a survivin promoter‐regulated adenovirus, displaying the ligand, provided effective oncolysis of pancreatic ductal adenocarcinoma in a preclinical study. In this study, we found that this adenovirus showed an even higher gene transduction efficiency and oncolytic potency for pancreatic neuroendocrine tumors in vitro, in a mouse model, and using clinical specimens of various human cancers. The data suggest that the virus, AdSur‐SYE, is a promising next‐generation therapy agent for pancreatic neuroendocrine tumors. Abstract: Although oncolytic adenoviruses are promising cancer therapy agents, for effective oncolytic activity, viruses need to specifically infect and effectively replicate in cancer cells but not in normal cells. We have previously identified a pancreatic cancer‐targeting ligand, SYENFSA (SYE), by screening an adenovirus library displaying random peptides against human pancreatic cancer cells and reported that a survivin promoter‐regulated adenovirus, displaying the SYE ligand (AdSur‐SYE), provided effective oncolysis of pancreatic ductal adenocarcinoma (PDAC) in a preclinical study. As we examined the infectivity of AdSur‐SYE in human surgical specimens of various pancreatic tumors, we unexpectedly found that AdSur‐SYE showed high gene transduction efficiency for pancreatic neuroendocrine tumors (PNETs) as well as for PDAC, 9.1‐ and 6.2‐fold, respectively, compared to that of the nontargeting virus (AdSur). The infectivity of both vectors was almost the same in other cancers and organs such as the pancreas. Immunostaining indicated that the cells infected with AdSur‐SYE were PNET cells but not stromal cells. AdSur‐SYE showed a significantly higher oncolytic potency than that of AdSur in human PNET cell lines, and intratumoral infection with AdSur‐SYE completely diminished subcutaneous tumors in a murine model, in which AdSur‐SYE effectively proliferated and spread. AdSur‐SYE exerted a stronger oncolytic effect in primary PNET cells cocultured with mouse embryonic fibroblasts than AdSur did. Thus, AdSur‐SYE shows promise as a next‐generation therapy for PNET.